King of Bitter (Andrographis paniculata Nees) Somatic Embryogeni Callus Culture on MS Medium With Added by 2,4-D and BAP - Prihatini, Retno; K.Huda, Nadyatul; Idris, Muhamad (UNIVERSITAS NEGERI PADANG, 2024)
In this research we have studied about somatic embryogenesis derived on Sambiloto (Andrographis paniculata) cv. VGT callus culture by addition BAP (benzylamino purine) and 2,4-D (2,4 diclorophenoxyacetic acid) on MS (Murashige and Skoog) Medium. King of Bitter seeds were germinated on MS medium for 3 weeks, then the second leaf that full opened used as explants. The explant planting on medium with several concentration growth regulator (BAP combinated with 2,4-D) to callus induce. MS medium with added by 0.5 ppm BAP+ 0.5 ppm 2,4-D ( A treatment), 0.5. ppm BAP + 1 ppm 2,4-D (B treatment ), 0.5 ppm BAP + 1.5 ppm 2,4-D (C treatment ), 0.5 ppm BAP + 2 ppm 2,4-D (D treatment), each of treatment with 5 replications. The observation used descriptive method for callus texture, somatic embryo derived with it development fase after subcultured on MS medium with the same concrentration BAP and 2,4-D . The result showed that callus have formed on all of treatment (A, B,C and D), whereas callus with somatic embryogenesis only on C treatment, with the range of callus fresh weight (FW) were 0.6-1.0 g. After 3 weeks at second subcultured on MS medium with added 0.5 ppm BAP+ 1,5 ppm 2,4-D , somatic embryo development showed globular fase and heart shape fase .